B.R. AMBEDKAR AND HIS POLITICAL PHILOSOPHY - Dr. Karnika Dubey (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
As a renowned social reformer and an eminent intellectual, Dr.B. R. Ambedkar was truly concerned about the plight of the untouchables at the beginning of his career. His entire life was devoted to socio-economic development (Bakshi, 2009). Ambedkar’s revolutionary ideology helps to renegotiate in particular the crisis of western political theory and leads people’s struggles. Ambedkar emerged with the advent of a Dalit movement in modern times, Ambedkar emerged as a major political philosopher (Bakshi, 2009).Inthe early 1920s,he became prominent in the socio-political scenario of India. He played a pivotal role in the upliftment of the lowest level of so-called untouchable Indian society in respect to social, economic, political and religious perspectives. Besides, he made an outstanding contribution as an economist, sociologist, legal illuminator, educationist, writer, parliamentarian, advocate and human-right activist. He was an iconoclast and researcher who effectively mobilized, emergized, unified the untaught Indians against all social and political suppressions and oppressions. This study encapsulates the political philosophy of Ambedkar.